Resolution of inflammation: therapeutic potential of pro-resolving lipids in type 2 diabetes mellitus and associated renal complications - Borgeson, Emma; Godson, Catherine (Frontiers in Immunology, 2012)
The role of inflammation in the pathogenesis of type 2 diabetes mellitus (T2DM) and its associated complications is increasingly recognized. The resolution of inflammation is actively regulated by endogenously produced lipid mediators such as lipoxins, resolvins, protectins and maresins. Here we review the potential role of these lipid mediators in diabetes-associated pathologies, specifically focusing on adipose inflammation and diabetic kidney disease, i.e. diabetic nephropathy (DN). DN is one of the major complications of T2DM and we propose that pro-resolving lipid mediators may have therapeutic potential in this context. Adipose inflammation is also an important component of T2DM-associated insulin resistance and altered adipokine secretion. Promoting the resolution of adipose inflammation would therefore likely be a beneficial therapeutic approach in T2DM.